Chitosan-g-estrone Nanoparticles of Palbociclib Vanished Hypoxic Breast Tumor after Targeted Delivery: Development and Ultrasound/Photoacoustic Imaging - Mehata A.K.; Singh V.; Vikas N.; Singh N.; Mandal A.; Dash D.; Koch B.; Muthu M.S. (My University, 2025)
Breast cancer is the leading cause of death among women globally. Approximately 80% of all breast cancers diagnosed are overexpressed with estrogen receptors (ERs). In this study, we have developed an estrone (Egen)-grafted chitosan-based polymeric nanocarrier for the targeted delivery of palbociclib (PLB) to breast cancer. The nanoparticles (NPs) were prepared by solvent evaporation using the ionic gelation method and characterized for particle size, zeta potential, polydispersity, surface morphology, surface chemistry, drug entrapment efficiency, cytotoxicity assay, cellular uptake, and apoptosis study. The developed PLB-CS NPs and PLB-CS-g-Egen NPs had a particle size of 116.3 ± 1.53 nm and 141.6 ± 1.97 nm, respectively. The zeta potential of PLB-CS NPs and PLB-CS-g-Egen NPs was found to be 18.70 ± 0.416 mV and 12.45 ± 0.574 mV, respectively. The morphological analysis demonstrated that all NPs were spherical in shape and had a smooth surface. An in vitro cytotoxicity assay was performed in estrogen receptor (ER)-expressing MCF7 cells and T47D cells, which suggested that targeted NPs were 57.34- and 30.32-fold more cytotoxic compared to the pure PLB, respectively. Additionally, cell cycle analysis confirmed that cell cycle progression from the G1 into S phase was blocked more efficiently by targeted NPs compared to nontargeted NPs and PLB in MCF7 cells. In vivo pharmacokinetic studies demonstrated that entrapment of the PLB in the NPs improved the half-life and bioavailability by ∼2-3-fold. Further, ultrasound and photoacoustic imaging of DMBA induced breast cancer in the Sprague-Dawley (SD) rat showed that targeted NPs completely vanished breast tumor, reduced hypoxic tumor volume, and suppressed tumor angiogenesis more efficiently compared to the nontargeted NPs and free PLB. Further, in vitro hemocompatibility and histopathology studies suggested that NPs were biocompatible and safe for clinical use. © 2023 American Chemical Society.